Prostaglandin F2α influences pre-ovulatory follicle characteristics and pregnancy per AI in anovular dairy cows - Lopes, F. R. [UNESP]; Silva, L. M.; Zimpel, R.; Munhoz, A. K. [UNESP]; Vieira-Neto, A.; Pereira, M. H.C. [UNESP]; Poindexter, M.; Gambarini, M. L.; Thatcher, W. W.; Vasconcelos, J. L.M. [UNESP]; Santos, J. E.P. (Elsevier, 2020)
Objectives were to determine the effects of a dose of PGF2α administered 2 days before timed artificial insemination (AI) on LH pulsatility, characteristics of the pre-ovulatory follicle, and pregnancy per artificial insemination (P/AI) in anovular dairy cows, particularly in cows not subjected to hyperthermia. In experiment 1, 2,011 lactating Holstein cows had ovaries scanned by ultrasound to determine corpus luteum (CL) presence and only those without a CL in two consecutive exams were enrolled (n = 437). Cows had the estrous cycle synchronized with an estradiol-progesterone based protocol starting on experiment Day −11 and timed AI on Day 0. Cows were assigned randomly to receive a single dose of 25 mg of PGF2α as dinoprost on Day −4 (1PGF, n = 222) or two doses of 25 mg each of PGF2α, one on Day −4 and one on Day −2 (2PGF, n = 215). Rectal temperatures were evaluated on the day of AI and 7 days later and cows were classified as being normothermic (<39.1 °C) or hyperthermic (≥39.1 °C). Ovulatory responses and P/AI were determined. In experiment 2, cows with regressed CL were exposed to low concentrations of progesterone and then randomly assigned to the same estrous synchronization protocol and treatments, 1PGF (n = 28) and 2PGF (n = 28). Blood was sampled and analyzed for concentrations of progesterone, and for concentrations of LH and 13,14-dihydro-15-keto-PGF2α metabolite (PGFM) every 15 min starting 1 h before to 6 h after treatments and then every 2 h from 12 to 59 h after treatments. The pre-ovulatory follicle was aspirated 44 h after treatments and concentrations of estradiol quantified. In experiment 1, treatment of anovular cows with a second dose of PGF2α increased P/AI in normothermic cows (19.8 [18/91] vs. 38.8% [31/80]), but not in hyperthermic cows. Synchronization was not affected by treatment, but it was greater for normothermic than hyperthermic cows (87.1 [149/171] vs. 77.8% [207/266]). When only synchronized cows were evaluated, the same responses were observed; treatment with 2PGF increased P/AI compared with 1PGF in normothermic cows (23.1 [18/78] vs. 43.7% [31/71]), but not in hyperthermic cows. In experiment 2, administration of 25 mg of dinoprost in 2PGF resulted in concentrations of PGFM 26-fold greater than 1PGF in the first 6 h after treatment (48 vs. 1,242 pg/mL). Cows receiving 2PGF had smaller basal LH concentration (0.57 vs. 0.46 ng/mL) and less frequent LH pulses (4.5 vs. 3.9 pulses/6 h), but duration of the LH surge was longer for 2PGF than 1PGF (13.1 vs. 15.5 h). Treatment with 2PGF increased the diameter and volume of the pre-ovulatory follicle, and concentration of estradiol (115 vs. 262 ng/mL) and total follicular estradiol content (124 vs. 505 ng) compared with 1PGF. Collectively, these results suggest that PGF2α has a role in fertility of anovular cows that is unrelated to its luteolytic effect.
Keywords: Anovular; Dairy cow; Follicle; Prostaglandin